A new variety of Crotalaria prostrata Roxb. (Fabaceae) from the Northern Western Ghats, India - Rokade, Krishnat; Dalavi, Jagdish Vishnu; Gaikwad, Nikhil; Yadav, Shrirang (Phytotaxa, 2019)
Crotalaria prostrata var. nigrisperma is described and illustrated as a new variety. The new variety is restricted to Northern Western Ghats of India. It is an annual, decumbent, sparingly branched herbs with strigose hairy stem, densely hirsute pods and dark black polished seeds. The taxon differs from both the varieties of Crotalaria prostrata viz. C. prostrata var. prostrata and C. prostrata var. levis in some morphological characters such as habit, stem indumentum, pod stalk, pod surface and colour of the seeds.